2019
DOI: 10.1097/bpb.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fatty infiltration of the multifidus muscle in patients with adolescent idiopathic scoliosis through evaluation by magnetic resonance imaging compared with histological analysis: a diagnostic accuracy study

Abstract: To evaluate fat infiltration in the multifidus muscle close to the scoliotic curve as seen in MRI compared with the histological evaluation in patients with adolescent idiopathic scoliosis (AIS). The evaluation of fatty infiltration in the multifidus muscle of patients with AIS by MRI was compared with biopsy. Fatty infiltration was greater in concave side than in the convex side in both MRI (P=0.005) and biopsy evaluation (P=0.026). There was no correlation between the fatty infiltration findings evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
5
10
0
1
Order By: Relevance
“…In recent decades, there have been multiple reports of bilateral PSM asymmetry [ 2 , 5 11 ]. Abnormal hyperintense signal of PSM has been identified on the concave side by magnetic resonance imaging [ 2 , 11 ], which was consistent with the histologic finding of increased fibrosis and fatty infiltration on concavity [ 6 , 9 ]. Increased electrical activity of PSM was also found on the convex side [ 8 , 10 ].…”
Section: Introductionsupporting
confidence: 62%
“…In recent decades, there have been multiple reports of bilateral PSM asymmetry [ 2 , 5 11 ]. Abnormal hyperintense signal of PSM has been identified on the concave side by magnetic resonance imaging [ 2 , 11 ], which was consistent with the histologic finding of increased fibrosis and fatty infiltration on concavity [ 6 , 9 ]. Increased electrical activity of PSM was also found on the convex side [ 8 , 10 ].…”
Section: Introductionsupporting
confidence: 62%
“…Our findings related to tissue composition are consistent with prior studies, although again only two prior studies have made compositional comparisons between concave and convex sides of scoliotic curvature in AIS. In both studies, elevated levels of collagen 17 and fatty infiltration 17,18 were found on the concave side of the scoliotic curve. In addition, Wajchenberg et al 18 reported that they found no relationship between amount of histologically observed fatty infiltration and curve severity.…”
Section: Discussionmentioning
confidence: 87%
“…In both studies, elevated levels of collagen 17 and fatty infiltration 17,18 were found on the concave side of the scoliotic curve. In addition, Wajchenberg et al 18 reported that they found no relationship between amount of histologically observed fatty infiltration and curve severity. However, the actual proportions of fibrotic or fatty tissue relative to the sample area were not quantified in either of these studies, and comparisons were only made based on the number of samples demonstrating the “presence” or “absence” of what was considered abnormal infiltration, making absolute comparisons between our own data and prior literature difficult.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, our results also showed PS muscles had high percentages of FAPs of which were more adipogenic and had greater cell proliferation rates compared to the hindlimb muscles. Clinically, PS muscles are known to develop FI in a number of spine conditions such as degenerative disc disease and scoliosis . Most studies of PS FI center on imaging quantification of FI and correlation to clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%